Millstones from the settlement complex of Aquincum: preliminary research - Láng, O; Wilson, A (Hungarian National Museum, 2023)
Excavations carried out in several parts of the settlement complex of Aquincum (legionary fortress, Military and Civil Towns, villa estates) have so far revealed 250 complete or fragmentary hand querns and millstones of different types. Most were discovered reused in secondary contexts, but some were found in their original position (i.e. in the courtyards of town houses or villas).The cataloguing of this group of finds has just been completed (although new ones continue to be found in ongoing excavations), and therefore detailed research on the types, material, and economic significance has only just begun (in a cooperation between the University of Oxford and the BHM Aquincum Museum). This paper presents the preliminary results of this work on the find location and dating of these stones, as well as distinguishing between hand querns and water-mills. It explores the potential of this neglected group of Aquincum finds, and especially what they might suggest about the extent of the use of water-powered milling on the Roman frontier in Pannonia.